Choosing the fitness function for the job: Automated generation of test suites that detect real faults. (16th November 2020) - Salahirad, Alireza; Almulla, Hussein; Gay, Gregory
Abstract : The article from this special issue was previously published in Software Testing, Verification and Reliability, Volume 29, Issue 4–5, 2019. For completeness we are including the title page of the article below. The full text of the article can be read in Issue 29:4–5 on Wiley Online Library: https://onlinelibrary.wiley.com/doi/10.1002/stvr.1701